Incremental LM-Cut - Pommerening, Florian; Helmert, Malte (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
In heuristic search and especially in optimal classical planning the computation of accurate heuristic values can take up the majority of runtime. In many cases, the heuristic computations for a search node and its successors are very similar, leading to significant duplication of effort. For example most landmarks of a node that are computed by the LM-cut algorithm are also landmarks for the node’s successors. We propose to reuse these landmarks and incrementally compute new ones to speed up the LM-cut calculation. The speed advantage obtained by incremental computation is offset by higher memory usage. We investigate different search algorithms that reduce memory usage without sacrificing the faster computation, leading to a substantial increase in coverage for benchmark domains from the International Planning Competitions.